Halal Food Application Usage and Acceptance among Muslim Students in South Korea - Oktaviana, Fadilla; Hidayat, Syarif (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2024)
Halal food is a crucial concern for Muslim students in countries with a minority Muslim population, such as South Korea, where less than 35,000 Muslims reside among a predominantly non-religious population. To address halal food accessibility, various applications have been developed. This study identifies the most commonly used halal food applications by Muslim students in South Korea and evaluates their acceptance levels using a mixed-methods approach. Data were collected through interviews and questionnaires based on the Technology Acceptance Model (TAM). Findings indicate that Mufko (Halal Food Korea) and Mobpay (Halal Food Korea) are the most frequently used applications, both scoring in the “excellent” category for user acceptance. These applications are highlyeffective and strongly recommended for addressing the halal food needs of Muslim students in South Korea.